A Concise Update on the Relevance of Secretory Phospholipase A2 Group IIA and its Inhibitors with Cancer - Chen, Juan; Ye, Long; Sun, Yu; Takada, Yoshikazhu (Medicinal Chemistry, 2017)
Secretory phospholipase A2 group IIA (sPLA2-IIA) is an enzyme that hydrolyzes the sn-2 ester bond in glyceroacyl phospholipids present in lipoproteins and cell membranes. As many immunohistochemical studies reveal that the high expression of sPLA2-IIA in the tumorous tissue or plasma of cancer patients, though low expression in other cases, the enzyme is considered highly relevant with cancer development. Effort has been made to establish the mechanism of how sPLA2- IIA is involved in various cancers in order to understand its pathogenic role and to utilize it as a target for cancer diagnosis and therapy. This article specifically reviews recent studies regarding the relevance of sPLA2-IIA with various cancers and reported inhibitors of the protein.
Keywords: therapeutic strategy